Diagnostic Accuracy of MRI in Patients with Elevated PSA Levels in Predicting Prostatic Carcinoma, Keeping Histopathology as Gold Standard - Muhammad Mohsin Kamal Shah, Mushaib Muhammad Khan, Warda Sattar, Reeta Rani, Fareeha Shahid, Aburabee Ai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prostate cancer remains one of the most frequently diagnosed malignancies in men, where early detection plays a vital role in improving treatment outcomes. Elevated levels of prostate-specific antigen (PSA) often necessitate additional diagnostic assessments, with magnetic resonance imaging (MRI) emerging as a non-invasive and effective tool for evaluation. Objective: This study aimed to assess the diagnostic accuracy of MRI in identifying prostate cancer among patients with elevated PSA levels, using histopathology as the gold standard. Material and Methods: The study was conducted as cross-sectional validation study at the Shaheed Mohtarma Benazir Bhutto Medical College, Lyari, Karachi, during the six month period from January, 2022 to June, 2023. Two hundred and thirty of the patients with PSA levels at >4 ng/mL underwent prostate MRI, and if biopsy proved histopathologically positive, transrectal ultrasound guided biopsy was performed. Statistical analysis was performed in SPSS version 26.0 and key diagnostic measures, including sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were determined. Results: MRI demonstrated a sensitivity of 92.3% and specificity of 54.1%, with a PPV of 80.9% and an NPV of 76.9%. The overall diagnostic accuracy was 79.6%, and the chi-square test (p < 0.001) indicated a significant association between MRI results and histopathology findings. Conclusion: MRI exhibited high sensitivity and negative predictive value, supporting its utility as a screening tool for prostate cancer detection in patients with elevated PSA levels. However, its moderate specificity highlights the need for histopathological confirmation or the use of advanced imaging modalities to minimize false-positive results. Keywords: Prostate cancer, MRI, PSA levels, Diagnostic accuracy, Histopathology, Sensitivity, Specificity.